Trade Goods and Nations in Sagard's Dictionary: A St. Lawrence Iroquoian Perspective - Steckley, John (Ontario History, 2012)
The disappearance of the St. Lawrence Iroquoians, between the time Jacques Cartier encountered them in the 1530s to the arrival of the French permanently at the beginning of the seventeenth century has long been speculated on by historians and anthropologists. In this article linguistic evidence coming from the dictionary compiled by Recollect Brother Gabriel, based on his stay with the Huron in 1623 and 1624 is used to suggest that at least one of his linguistic informants was a St. Lawrence Iroquoian who had come to join the Huron, a path followed by others of his nation as well.